2022
DOI: 10.3389/fphar.2022.893422
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Type 5 Metabotropic Glutamate Receptor: A Potential Therapeutic Strategy for Neurodegenerative Diseases?

Abstract: The type 5 metabotropic glutamate receptor, mGlu5, has been proposed as a potential therapeutic target for the treatment of several neurodegenerative diseases. In preclinical neurodegenerative disease models, novel allosteric modulators have been shown to improve cognitive performance and reduce disease-related pathology. A common pathological hallmark of neurodegenerative diseases is a chronic neuroinflammatory response, involving glial cells such as astrocytes and microglia. Since mGlu5 is expressed in astro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 231 publications
(273 reference statements)
0
9
0
Order By: Relevance
“…Several other mGluR5 regulated mechanisms could potentially modulate recovery after stroke, 16 , 88 such as changes in growth factor levels including BDNF, 71 , 89 brain inflammation 35 or axogenesis. 90 , 91 Further research is needed to understand the mechanisms underlying the enhancement of recovery by mGluR5 NAMs after stroke.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several other mGluR5 regulated mechanisms could potentially modulate recovery after stroke, 16 , 88 such as changes in growth factor levels including BDNF, 71 , 89 brain inflammation 35 or axogenesis. 90 , 91 Further research is needed to understand the mechanisms underlying the enhancement of recovery by mGluR5 NAMs after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, because we show that mGluR5 is present in relevant regions of injured brain tissue in stroke patients, they may be amenable to therapeutic interventions. Still, outside of stroke, the clinical effects of mGluR5 NAMs in other brain disorders depend on context, dose and timing, 35 which has implications for the clinical trial design of these compounds in stroke recovery. Translating preclinical findings into successful clinical trials has generally been unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mGluRs are G-protein-coupled receptors that regulate glutamate neurotransmission. Activation of certain mGluR subtypes, particularly mGluR5, has been implicated in HD pathology [130,131]. Animal studies have shown that mGluR5 antagonists can activate autophagy through convergent mechanisms, promoting the clearance of mHTT aggregates and reducing neurodegeneration in HD models [132].…”
Section: Glutamate Receptor Modulationmentioning
confidence: 99%